Properties and Interconnectedness of Valencian Blogs - Baviera-Puig, Tomás (Anàlisi, 2011)
Blogs constitute a publishing tool in Internet, available to any user. Moreover, they give a chance of connecting to other users through a specific dynamism. The blogosphere is getting on like that. For the particular case of Valencian Community (Spain), we analyze the reality of these interconnecting possibilities of blogs written by users from this geographical space.